Kebutuhan Air dan Jaringan Air Bersih Desa Napal Kabupaten Musi Banyuasin - Ayu Marlina; Reni Andayani (Universitas Islam 45, 2020)
The provision of clean water is one of main priority for human life and health. it is not only prioritized in the cities but also in the rural areas. Clean water supply system is carried out by piping and non-piping systems. Whereas the piping system is managed by Perusahaan Daerah Air Minum (PDAM), the non-piping system is managed by the community both individually and in groups. The clean water network in Desa Napal, Musi Banyuasin still uses a non-piping system and does not have a clean water network yet from the PDAM. The purpose of this study is to determine the clean water needs of Desa Napal both domestic and non-domestic and rural network planning of water supply through the Waternet program. The research methodology began with literature study, gathering information from survey, primary data collection in the form of non-domestic building data and pipe depth points, secondary data collection in the form of location maps, population and domestic buildings. Furthermore, the calculation of water needs and planning of the clean water network of Napal Village was done using the Waternet program. Results found that the total water needs of Napal village was 2.228 liters/second or can used water flow of 6 liters/second as planning. The clean water network in Napal village was planned to use pipe diameter of 50, 80, and 150. The pipeline network (Pressure/atm) in the Waternet program was ≤ 2, which showed that the network runs well.